Harmonic structure of tracheal biometrics - Milavec, Dinko (Array, 2020)
According to existing research, in 20% of patients the required tracheal size (diameter and length) could not be measured automatically (using software solution). In this paper, we use Zederbauer's harmonic circle to define the relationship between a person's body height and the diameter and length of their trachea. We then explore differences by gender. The results show that there is a highly significant correlation between measured data and values obtained by harmonic analysis. The final goal is to obtain the mathematical interpretation of the relationship of the tracheal size to the height of man, in order to further apply such sizes in the creation of 3D models that could finally be printed on appropriate 3D printers and with the suitable material.